2022
DOI: 10.2118/209603-pa
|View full text |Cite
|
Sign up to set email alerts
|

Intense Cooling during Composite Rock Breaking of High-Pressure CO2 Jet-Polycrystalline Diamond Cutter

Abstract: Summary In deep well drilling, rock breaking has some problems, such as low rock breaking efficiency, serious thermal wear of cutters, short service life, and high cost. It is noticed that the application of CO2 drilling fluid in the oil and gas underbalanced drilling is an efficient approach to achieve the reduction of CO2 emissions. Thus, based on the rock-breaking advantages of CO2 jetting, a new rock-breaking method of combing high-pressure CO2 jet and polycrystalline diamond cutter (PDC) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Therefore, we propose the composite rock-breaking of a highpressure CO 2 Jet & PDC cutter [23]. Combined with the completed research [24], it can be found that the composite rock-breaking of high-pressure CO 2 jet & PDC cutter can effectively inhibit the heat generation of PDC cutter, reduce the thermal wear rate of the PDC cutter, and also improve the capacity of drill bit cleaning and debris carrying. Through the preliminary experimental research, the experiment of composite rock-breaking was designed, and the principle of the experiment is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we propose the composite rock-breaking of a highpressure CO 2 Jet & PDC cutter [23]. Combined with the completed research [24], it can be found that the composite rock-breaking of high-pressure CO 2 jet & PDC cutter can effectively inhibit the heat generation of PDC cutter, reduce the thermal wear rate of the PDC cutter, and also improve the capacity of drill bit cleaning and debris carrying. Through the preliminary experimental research, the experiment of composite rock-breaking was designed, and the principle of the experiment is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%